Preterm premature rupture of membranes: correlates and pregnancy outcome in a tertiary care setting - Rajan, Reeti; Menon, Vrinda (International Journal of Research in Medical Sciences, 2017)
Background: Prelabour membrane rupture before 37 weeks of gestation is referred to as preterm premature rupture of membranes (PPROM). Incidence of PPROM is about 2% of all pregnancies. This prospective study aims to determine fetal and early neonatal outcome of pregnancies with PPROM. Methods: The study was conducted in 190 antenatal women with PPROM between 24 weeks to 36weeks of gestation over a period of 18 months. Their babies were followed up till discharge from Pediatric new born unit. Results: Prevalence of PPROM was 0.8%, accounting for 19% of preterm deliveries. 61% of women with PPROM showed evidence of lower genito-urinary tract infection, 28% had anemia, 48% gave history of coitus during pregnancy. Mean gestational age of membrane rupture was 32 weeks, the mean latency between membrane rupture and delivery was 4.4 days. Chorioamnionitis developed in 13% of women with PPROM, cord prolapse in 4% and abruption in 3%. The gestational age wise survival was 40% in babies weighing less than 1.5kg, 88% in babies weighing 1.5 to 2.5kg and 93% in those more than 2.5kg. The predominant causes of neonatal mortality were hyaline membrane disease (HMD) in babies born before 28 weeks, HMD and sepsis between 29 to 33 weeks and sepsis in babies born after 34 weeks. Conclusions: Screening and treatment of risk factors may contribute to prevention of PPROM. Neonatal survival depends on gestational age and availability of advanced NICU facilities. Patients and family members should be counseled regarding the outcome of pregnancies with PPROM. A team effort by the obstetrician and neonatologist in a tertiary care setting can ensure a healthy and fruitful life for mother and baby.